Evidências de lean healthcare em hospitais brasileiros - Costa, Luana Bonome Message (Universidade Federal de São Carlos, 2015)
Studies show that healthcare sector in Brazil is a highlighted sector in the current scenario of the country, mainly due to dissatisfaction of the population with respect to the services provided. This sector is under continuous pressure to improve services and patient safety and reduce costs, waiting times, and errors. In view of this scenario, it is evident the importance of research that present strategies and tools to assist the healthcare sector to improve its performance in Brazil, Lean is one of these strategies. To assess the state of the art on the subject, it was performed a review, classification and analysis of the literature, aiming to update the literature reviews of Mazzocato et al. (2010) and Souza (2009), and thus present the current developments in the subject area. To better understand the Lean Healthcare implementation process, and the benefits gained from such implementation, a case study was conducted in two Brazilian hospitals. It was studied two sectors of Hospital-Case A: Sterile Services Department and Pharmacy; and three sectors of Hospital-Case B: Chemotherapy, Operating Room and Radiotherapy. The analysis of the cases and the literature reviewed shows that it is important to use Lean tools in a logical and structured manner; the barriers and critical factors to the success of Lean implementation are associated with human factor and cultural changes; and the results obtained indicate that the work is targeted to reduce the lead time (patient and information), increased capacity and improved financial performance.
Keywords: Saúde - administração; Hospitais; Produção enxuta; Lean healthcare; Lean manufacturing; Lean hospital; ENGENHARIAS::ENGENHARIA DE PRODUCAO